The Sources of Strength Australia Project: study protocol for a cluster randomised controlled trial. Issue 1 (December 2016) - Calear, Alison; Brewer, Jacqueline; Batterham, Philip; Mackinnon, Andrew; Wyman, Peter; LoMurray, Mark; Shand, Fiona; Kazan, Dominique; Christensen, Helen
Abstract Background The school system has been identified as an ideal setting for the implementation of prevention and early intervention programs for suicide. However, in Australia, suicide-prevention programs that are routinely delivered in the schools are lacking. Internationally, evidence exists for the effectiveness of peer-led interventions that take a social connectedness approach to improve help-seeking for suicide. The aim of the current trial is to test the effectiveness of the Sources of Strength program to promote help-seeking for suicide in adolescents in Australian high schools. Methods/design This study is a two-arm, cluster-randomised, controlled trial that will compare the evidence-based Sources of Strength program to a wait-list control condition. Sixteen Australian high schools will be recruited to the trial, with all adolescents in years 7 to 10 (12–16 years of age) invited to participate. Peer leaders from intervention-condition schools will receive training in the Sources of Strength program and will integrate positive messages, across 3 months, with the support of adult advisors. Activities may take the form of class presentations, posters, videos, and messages on social media sites and will aim to change help-seeking norms, strengthen youth-adult connections, and promote positive coping. The primary outcome measure for the study is help-seeking intentions, whereas secondary outcomes include help-seeking behaviour, help-seeking attitudes and norms, referral of distressed peers, availability of adult help, positive coping, and suicidal behaviour. Data will be collected pre-intervention, post-intervention (after the initial 3 months of messaging), and at the end of the first (6-month follow-up) and the second year after implementation (18-month follow-up). Primary analyses will compare changes in help-seeking intentions for the intervention condition relative to the wait-list control condition using mixed-effect repeated-measures analyses to account for clustering within schools. Discussion If proven effective, this universal social connectedness program for suicide could be more widely delivered in Australian high schools, providing a valuable new resource. The Sources of Strength program has the potential to significantly contribute to the mental health of young people in Australia by improving help-seeking for suicide. The findings from this research will also contribute to the evidence-base for peer-leadership programs internationally. Trial registration Australian New Zealand Clinical Trials Registry, ACTRN12616000048482 . Registered on 19 January 2016.